2015
DOI: 10.1513/annalsats.201410-463oc
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and Tumor Necrosis Factor-α Are Associated with Quality of Life–Related Symptoms in Pulmonary Arterial Hypertension

Abstract: IL-6 and tumor necrosis factor-α levels are associated with certain quality of life domains in patients with pulmonary arterial hypertension. Clinical trial registered with www.clinicaltrials.gov (NCT00384865).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…42 However, higher IL-6 levels in this population were linked to increased fatigue, anxiety and depression. 43 Our pilot data provide preliminary evidence that slow-paced respiration may decrease IL-6 levels leading to improved depressive symptoms and fatigue. Sleep loss can result in increased proinflammatory cytokines (IL-6) and poor sleep quality.…”
Section: Discussionmentioning
confidence: 66%
“…42 However, higher IL-6 levels in this population were linked to increased fatigue, anxiety and depression. 43 Our pilot data provide preliminary evidence that slow-paced respiration may decrease IL-6 levels leading to improved depressive symptoms and fatigue. Sleep loss can result in increased proinflammatory cytokines (IL-6) and poor sleep quality.…”
Section: Discussionmentioning
confidence: 66%
“…In animal models, PH development has been seen after the administration of recombinant IL-6 and also in IL-6 transgenic mice [103][104][105], whereas IL-6 knockout mice have shown resistance to hypoxia-induced PH development [106]. In clinical studies, IL-6 has shown to correlate to survival and quality of life in IPAH patients [80,107] and in predicting long-term responses to PEA in CTEPH patients [98]. In a recent study, cytokine clusters were made in PAH patients using machine learning.…”
Section: Inflammatory Diagnostic and Prognostic Biomarkers In Pah Andmentioning
confidence: 99%
“…Since substantially elevated circulating levels of certain inflammatory mediators, including IL-6, have been found to correlate with worse clinical outcomes, quality of life-related symptoms, and/or death in PAH patients (3)(4)(5), the sustained inflammation in PAH has moved from a common histopathological finding to a potential contributor to the perpetuation of the disease. However, the field is currently lacking a mechanistic vantage point to understand how inflammation, and in particular IL-6-dependent signaling, contributes to the disease pathogenesis, a prerequisite for the development of novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IL-6-overexpressing mice spontaneously develop PH and pulmonary vascular remodeling, whereas Il6-knockout mice are more resistant to the development of PH induced by chronic hypoxia (11,12). In this context, although blockade of IL-6 signaling represents a promising target (3,4,(9)(10)(11)(12)(13)(14), it remains unclear how this signaling pathway determines the progression and ultimately the severity of the disease, and it is therefore difficult to develop therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%